Proyecto de Factibilidad para la creación de una Empresa de Servicios de Recaudación y Pagos para la Parroquia Taquil Cantón y Provincia Loja - Robles Zeas, Paola Karolina (2016)
This project feasibility is a prerequisite for obtaining engineering degree in Banking and Finance, thus meet the academic rules of the university, and contribute to the project feasibility for creating a collection company and payments for the canton and parish Taquil Loja province, for the satisfaction of the needs of citizens and the timely payment of its obligations to comply with the same was made based on the following specific objectives. Mainly we had as general objective the project feasibility for the creation of a service company for collection and payments for Taquil parish. Specific objectives market analysis developed by determining the needs of the people of the parish and our offer consists of 972 services and unmet 31.061 our services to be provided; next target technical study was conducted focusing on our services installed by 24192 and capacity use in the first year of life of the project will be 80%, plus the location will be in the canton and province of Loja capacity Taquil parish in the neighborhood Wax "Central Plaza" 5 The next target was just took legal administration which determined that our company is not required to take sole accounting and bore the name of "SERVITRNSF"; After this goal the economic-financial study determining income and expenses $ 9.676,80 $9287.40 that the company will for the first year with an investment of $ 5.887,28 and the cost benefit ratio was determined which is $ 0.18 cent gain and a payback period of four years with investment 21 days. For the project the following materials and methods were used: Scientific allowed to establish the logical processes; Helped deductive categorization of information; Inductive who helped the understanding of the factors influencing the economic and financial development; Analytical enabled analysis of the results; Math was the appropriate use of each of the formulas to determine if the company is feasible, concluding with mention that the project is entirely feasible laughing benefits the company owns and recommending that more services for users are included.